Juntas híbridas TPU/AA6061-T6 moldadas por injeção com alta resistência interfacial via tratamentos de superfície baseados em silano - Vasconcelos, Rayana Larissa (Universidade Federal de São Carlos, 2025)
The fabrication of polymer-metal hybrid structures with high mechanical performance is related to the constituent materials of such structure, as well as the surface treatments applied to promote polymer-metal adhesion. In this work, thermoplastic polyurethane (TPU) and 6061-T6 aluminum alloy hybrid joints with high interfacial strength were developed by injection overmolding, with metal inserts treated consecutively by abrasion, oxidation and silanization, using different solution concentrations and pH, and a post-molding heat treatment. Metal inserts treated with 2% v/v and pH 10 presented a more hydrophilic surface compared to untreated metal inserts, which contributed to the subsequent polymer-metal adhesion. Analysis of the hybrid joints cross-section indicated the formation of an aluminum oxide layer and a partial TPU infiltration into microcavities on the metal surface. In shear testing, the hybrid joints showed an asymptotic mechanical behavior, in which the force increased continuously up to approximately 3 mm of displacement and, from that point on, remained nearly constant until failure. This suggests that, up to 3 mm of displacement, the measured force is equivalent to the interfacial strength of the hybrid joints. From 3 mm, the TPU intrinsic mechanical strength began to show a more considerable influence on the mechanical behavior of the hybrid joints, since as the material reached its yield point. From 3 mm until the moment of failure, the measured force became a function of the plastic deformation of the TPU. Therefore, the interfacial strength of the hybrid joints was greater than the intrinsic mechanical strength of the TPU, proving the efficiency of the surface treatments applied in the adhesion and performance of the TPU/AA6061-T6 hybrid joints.
Injection molded TPU/AA6061-T6 hybrid joints with high interfacial strength by silane-based surface treatments
Keywords: Sobremoldagem por injeção; Estrutura híbrida de polímero-metal; Poliuretano termoplástico; Adesão; Injection overmolding; Polymer-metal hybrid structure; Thermoplastic polyurethane; Adhesion; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS; 9. Indústria, Inovação e Infraestrutura